Impact of European Bison Grazing (Bison bonasus (L.)) on Species and Functional Traits of Carabid Beetle Assemblages in Selected Habitats in Poland - Axel Schwerk; Daniel Klich; Elżbieta Wójtowicz; Wanda Olech (Biology, 2021)
Currently we are observing a drastic decline in insect fauna on a large scale. Grazing is regularly used as an ecological method of protecting or restoring special biotopes that are important for species conservation. The European bison (Bison bonasus (L.)) is the largest living wild terrestrial animal in Europe; therefore, a large impact on flora and fauna as a result of its grazing activity can be assumed. There might be potential for implementing conservation measures that employ active grazing. Therefore, a study on a free-ranging European bison population and captive herds in enclosures was carried out in order to determine whether European bison grazing has an impact on carabid beetle assemblages and whether the degree of this impact (if any) depends on the intensity of grazing. No notable influence on numbers of individuals of carabid beetles could be detected, but there was an indication that high-intensity grazing may cause an increase in the number of species. Increased intensity of grazing seems to have only a weak impact on the species assemblage structure, but it has a stronger impact on the composition of functional traits in the assemblage, as demonstrated in particular by the significant impact of captive herds. The stronger relation between grazing intensity and the functional traits of the carabid beetle assemblages than between grazing intensity and assemblage structure indicates that using European bison grazing as a method of ecological engineering in the context of nature conservation may have more potential in regulating properties and functions of the ecosystem than in the conservation of specific species or species assemblages of carabid beetles.